Dakwah Via Youtube? Evolving Dynamics of Religious Communication in Aceh Islamic Society - Meriza, Iin; Febriani, Asra; Tisa, Mutia; Nurdin, Muhammad Riza (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The progress of information technology is currently very rapid. Any information can be received directly by the public in a matter of seconds via various social media. The YouTube platform is one of the social media that is popular with the public and is a good opportunity for da'wah activities. Da'i in Aceh took part in utilizing the YouTube platform as a medium for da'wah. This research aims to find out the information related to the use of the YouTube platform as a medium for da'wah in Aceh and knowing the character of da'wah by using the YouTube platform in Aceh. This research is field research using a qualitative approach. In determining research subjects, the author used purposive sampling so that researchers could gather information from users of the YouTube platform as a medium for preaching, especially YouTube channels that already exist among the public. The research results show that the aim of using the YouTube platform as a da'wah media in Aceh is to contribute to knowledge in institutions, unite alumni/organizations, store da'wah documentation, narrow down entertainment content, and expand the da'wah network. This article aims to explore the use of YouTube as a medium for da'wah in the post-modern era in Aceh, where da'wah is experiencing very rapid development. Furthermore, in this article the author exposes YouTube preaching content that can be accessed by various groups.